2012
DOI: 10.1308/003588412x13171221501663
|View full text |Cite
|
Sign up to set email alerts
|

The use of pre-operative computed tomography in the assessment of the acute abdomen

Abstract: INTRODUCTION While there are a lot of data on the accuracy of computed tomography (CT) in diagnosing specific causes of an acute abdomen, there is very little information on the accuracy of CT in the acute general surgical admissions workload. We look at the diagnostic accuracy of CT in patients presenting with an acute abdomen who ultimately required a laparotomy. METHODS Patients who underwent an emergency laparotomy between 2008 and 2010 at Eastbourne District General Hospital with pre-operative CT on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…[12][13][14] The results are also in keeping with reports of specific acute abdominal diagnoses such as appendicitis with an accuracy of 80.6-99%, [15][16][17] gastrointestinal perforation with an accuracy of 86%, 18 bowel ischaemia with an accuracy of 79.17-81%, 19,20 diverticulitis with an accuracy of 98% 21 and bowel obstruction with an accuracy of 65-97%. [22][23][24][25][26] However, the variable accuracy related to anatomical location of the pathology has not been described.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…[12][13][14] The results are also in keeping with reports of specific acute abdominal diagnoses such as appendicitis with an accuracy of 80.6-99%, [15][16][17] gastrointestinal perforation with an accuracy of 86%, 18 bowel ischaemia with an accuracy of 79.17-81%, 19,20 diverticulitis with an accuracy of 98% 21 and bowel obstruction with an accuracy of 65-97%. [22][23][24][25][26] However, the variable accuracy related to anatomical location of the pathology has not been described.…”
Section: Discussionsupporting
confidence: 77%
“…12 The overall accuracy of the initial CT report by either registrar or consultant was 81%, which improved to 93% following review by a second consultant, although this difference was not significant (p 5 0.15). These findings are therefore consistent, and indeed again, no significant difference was found to be related to radiologist grade.…”
Section: Discussionmentioning
confidence: 84%
“…The diagnostic performance parameters in our study were similar to those quoted by previous studies. [1][2][3] We demonstrate that CT scanning of the acute abdomen improves diagnostic performance. In patients who are acutely unwell, however, CT scanning should not delay commencement of treatment, be it medical or surgical.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, the duration of symptoms and signs of acute abdomen do not affect the sensitivity of CT scanning assessment. 1 Separate studies by Weir-McCall et al 2 and Taourel et al 3 have reported the accuracy of CT scanning in detecting the causes of acute abdomen to be 93% and 95%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In other centres, particularly overnight, radiology registrars may be responsible for interpreting the scans and for seeking consultant opinion when they feel necessary. Reassuringly, a recent UK study, assessing the diagnostic accuracy of CT in patients who underwent emergency laparotomy having presented with an acute abdomen, found no difference in the diagnostic accuracy of the initial registrar CT report compared to consultant reinterpretation [ 25 ]. Similarly a study of after-hours reporting by senior registrars demonstrated a comparable 92% accuracy of registrar CT reporting with a higher discrepancy rate actually being made within working hours [ 26 ].…”
Section: Discussionmentioning
confidence: 99%